Early Speech Segmentation in French-learning Infants: Monosyllabic Words versus Embedded Syllables. (September 2015) - Nishibayashi, Léo-Lyuki; Goyet, Louise; Nazzi, Thierry
Lexical acquisition relies on many mechanisms, one of which corresponds to segmentation abilities, that is, the ability to extract word forms from fluent speech. This ability is important since words are rarely produced in isolation even when talking to infants. The present study explored whether young French-learning infants segment from fluent speech the rhythmic unit of their native language, the syllable. Using the Headturn Preference Procedure and the passage word order, we explored whether these infants can segment monosyllabic words (at 6 and 8 months), syllables embedded in bisyllabic words (at 6 months) and bisyllabic words (at 6 months). Our results bring direct evidence in support of the early rhythmic segmentation hypothesis, by establishing syllabic segmentation both for monosyllabic words and embedded syllables at 6 months, while failing to find segmentation of bisyllabic words at the same age. They also indirectly extend to French previously reported effects of coarticulation, acoustic variation and infant-directed speech on segmentation found in English. Therefore, our study contributes to a better understanding of the similarities and differences in early segmentation across languages, and thus to a better understanding of the mechanisms underlying segmentation.